Surgical treatment for hydrosalpinx prior to in‐vitro fertilization embryo transfer: a network meta‐analysis. (13th September 2016) - Tsiami, A.; Chaimani, A.; Mavridis, D.; Siskou, M.; Assimakopoulos, E.; Sotiriadis, A.
ABSTRACT: Objective: The presence of hydrosalpinx impairs the outcome of in‐vitro fertilization embryo transfer (IVF‐ET). Surgical methods to either aspirate the fluid or isolate the affected Fallopian tubes have been attempted as a means of improving outcome. The aim of this network meta‐analysis was to compare the effectiveness of surgical treatments for hydrosalpinx before IVF‐ET. Methods: An electronic search of MEDLINE, Scopus, Cochrane Central Register of Controlled Trials (Central) and the US Registry of clinical trials for articles published from inception to July 2015 was performed. Eligibility criteria included randomized controlled trials of women with hydrosalpinx before IVF‐ET comparing ultrasound‐guided aspiration of the fluid, tubal occlusion, salpingectomy or no intervention. Ongoing pregnancy was the primary outcome and clinical pregnancy, ectopic pregnancy and miscarriage were secondary outcomes. A random‐effects network meta‐analysis synthesizing direct and indirect evidence from the included trials was carried out. We estimated the relative effect sizes as risk ratios (RRs) and obtained the relative ranking of the interventions using cumulative ranking curves. The quality of evidence according to GRADE guidelines, adapted for network meta‐analysis, was assessed. Results: Proximal tubal occlusion (RR, 3.22 (95% CI, 1.27–8.14)) and salpingectomy (RR, 2.24 (95% CI, 1.27–3.95)) for treatment of hydrosalpinx were superior to no intervention for ongoing pregnancy. For an outcome of clinical pregnancy, all three interventions appeared to be superior to no intervention. No superiority could be ascertained between the three surgical methods for any of the outcomes. In terms of relative ranking, tubal occlusion was the best surgical treatment followed by salpingectomy for ongoing and clinical pregnancy rates. No significant statistical inconsistency was detected; however, the point estimates for some inconsistency factors and their CIs were relatively large. The small study number and sizes were the main limitations. The quality of evidence was commonly low/very low, especially when aspiration was involved, indicating that the results were not conclusive and should be interpreted with caution. Conclusions: Proximal tubal occlusion, salpingectomy and aspiration for treatment of hydrosalpinx scored consistently better than did no intervention for the outcome of IVF‐ET. In terms of relative ranking, proximal tubal occlusion appeared to be the most effective intervention, followed by salpingectomy. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd. Abstract : This article's abstract has been translated into Spanish and Chinese. Follow the links from theabstract to view the translations. This article has been selected for Journal Club. Clickhere to view slides and discussion points.